Menentukan Posisi Duduk Seseorang Di Meja Makan: Menerjemahkan Ungkapan At The Third Point On The Table - Jaya, Doni (Jurnal Penerjemahan, 2016)
Translating culture-bound expressions always poses a challenge for a translator, especially when the target culture does not share the same concept or expresses the concept in a different way. The translator needs to possess both sufficient knowledge about the source culture and skills in conveying the same concept in the target language by taking account of the text’s demand and target readers’ needs. This paper focuses on an English expression at the third point on the table taken from Chapter 2 of Philippa Gregory’s novel The Other Boleyn Girl to be translated into Indonesian. This expression is problematic because Indonesian does not have a special expression to represent the culture-bound concept conveyed by the original English expression. Linguistic analysis demonstrates that literal transtation would only produce a meaningless rendering in Indonesian. Sociocultural analysis demonstrates that the English expression refers to a specific seating position at a Western (European) formal dinner. Based on this information, a number of alternative renderings can be generated by means of paraphrase. Contextual analysis of the novel’s plot generates one relevant rendering, which is “di sebelah kanan Wolsey” (“on Wolsey’s right side”) based on several considerations. Although this rendering is more readily understandable by Indonesian readers, several losses are inevitable, such as the cultural color and ceremonial connotation imparted by the original expression. This simple case analysis shows that a translator may have to deal with culture-bound expressions which have to be rewritten or paraphrased using a new set of words whose literal meaning differs significantly from that of the constituent words of the original expression in order to make it meaningful to the target readers. Contextual adjustments are also needed to construct a rendering which is relevant to the text’s demand. Keywords: cultural translation, table manners, paraphrase, context